Analysis of a power/cooling cycle (ejector refrigeration cycle and kalina cycle) - SEÇKİN, CANDENİZ (My University, 2022)
In this present study, thermodynamic analysis of a power/refrigeration combined cycle (combination of Kalina cycle and ejector refrigeration cycle) is presented. Primary output of the combined cycle is power which is produced by the Kalina cycle. In the proposed design of the combined cycle, ejector refrigeration cycle is placed at the separator exit of the Kalina cycle where the temperature and pressure of the Kalina cycle working fluid are high, i.e. utility potential of the fluid is high. A heat transfer process occurs from Kalina cycle to ejector refrigeration cycle at the separator exit and hence, refrigeration is generated as the secondary output of the combined cycle. The effect of variation in temperature and pressure of the Kalina cycle at the separator exit on efficiency of the Kalina cycle and COP of the ejector refrigeration cycle are presented. Additionally, variation of refrigeration capacity and power production with separator exit temperature and pressure of the Kalina cycle is also reported. Working fluids of the Kalina cycle and ejector cycle are ammonia-water solution and R134a, respectively. Details of the mathematical procedure is given with details. Obtained results are extensively discussed to show the internal mechanism of the combined cycle and to enlighten the results.
Keywords: Combined cycle; Ejector Refrigertion cycle; Kalina cycle; efficiency; COP